ACTORS AFFECTING DEMAND IN THE TEACHER LABOUR MARKET IN RUSSIA - Anna S. Elkina; Ekaterina S. Shevchenko (Высшее образование в России)
The article analyzes market and non-market factors affecting demand for professors in the Russian higher education institutions. Some attention is also paid to the factors that influence the wage elasticity of the demand in the teacher labour market. The authors divide the factors that determine the demand in the market into two groups: extensive factors related to the changes in the demand for educational services ofhigher education institution and intensive factors related to the changes in workload of professors. To assess the importance of the factors affecting the labour market demand the correlation calculations were carried out.